Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrids for improved supercapacitor performance - Balan, Beena K.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (RSC Advances, 2013)
Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrid electrode material which integrates dual wall decoration and interfacial area tuning for supercapacitor applications has been devised based on a simple approach. This is achieved by decorating RuO2 nanoparticles of size ca. 2-3 nm along the inner and outer walls of a hollow carbon nanofiber (CNF) support (F-20RuO(2)). In the next step, a proton conducting polymer, phosphoric acid doped polybenzimidazole (PBI-BuI), interface is created along the inner and outer surfaces of this material. A 103% increase in the specific capacitance is obtained for RuO2-PBI hybrid material as compared to that of F-20RuO(2) at the optimum level of the polymer wrapping. Apart from the high specific capacitance, the RuO2-PBI hybrid materials exhibit enhanced rate capability and excellent electrochemical stability of 98% retention in the capacitance. Such a remarkably high activity can be primarily attributed to the efficient dispersion of active sites achieved by properly utilizing inner and outer surfaces of CNF. Apart from this, the facile routes for ion transport created as a result of PBI incorporation coupled with excellent interfacial contact between the RuO2 and the electrolyte resulting in the improved utilization of the active material also contribute to the improved activity. In addition to this, the synergistic effects of pseudocapacitive contribution from both the PBI-BuI and RuO2 also contribute to the redefined performance characteristics.

Characterizing the nanoclay induced constrained amorphous region in model segmented polyurethane-urea/clay nanocomposites and its implications on gas barrier properties - Rath, Sangram K.; Sudarshan, Kathi; Bhavsar, Rupesh S.; Kharul, Ulhas K.; Pujari, Pradeep K.; Patri, Manoranjan; Khakhar, Devang V. (Physical Chemistry Chemical Physics, 2016)
There has been an increasing recognition of the fact that purely geometric factors associated with clay platelet dispersion in a polymer matrix cannot adequately explain the barrier properties of polymer/clay nanocomposites. The objective of the present work is to understand the nanoclay induced structural changes in a polyurethane-urea matrix and clay dispersion at different length scales using segment-specific characterization techniques and implications of the same in gas barrier properties using He, N-2 and CO2 as probe molecules. Wide angle X-ray diffraction (WAXD) and positron annihilation life time spectroscopy (PALS) studies revealed nanoclay induced alterations in the chain packing of the amorphous soft segments of the polyurethane matrix at a molecular scale of a few Angstroms. The hard segment organization and the phase morphology of the nanocomposites, spanning length scales of several nanometers, were investigated by small angle X-ray scattering (SAXS), scanning electron microscopy (SEM) and atomic force microscopy (AFM). Furthermore, the presence of a constrained amorphous region surrounding the nanoclay was confirmed from AFM, WAXD and PALS results. Several pertinent structural variables from the gas transport point of view were deduced from these characterization techniques to understand the effect of the barrier properties in tandem with the clay dispersion morphology.

Chemically stable covalent organic framework (COF)-polybenzimidazole hybrid membranes: enhanced gas separation through pore modulation - Biswal, Bishnu P.; Chaudhari, Harshal D.; Banerjee, Rahul; Kharul, Ulhas K. (Chemistry-A European Journal, 2016)
Highly flexible, TpPa-1@PBI-BuI and TpBD@PBI-BuI hybrid membranes based on chemically stable covalent organic frameworks (COFs) could be obtained with the polymer. The loading obtained was substantially higher (50%) than generally observed with MOFs. These hybrid membranes show an exciting enhancement in permeability (about sevenfold) with appreciable separation factors for CO2/N-2 and CO2/CH4. Further, we found that with COF pore modulation, the gas permeability can be systematically enhanced.
Keywords: covalent organic frameworks; Gas separation; membranes; microporous materials; pore modulation

Chemodialysis of organic acids using ABPBI-based hollow fiber membranes - Gawas, Saroj; Alladi, Lavanya; Kharul, Ulhas K. (Journal of Membrane Science, 2024)
Organic acids are a class of essential commodity chemicals used in various industries. Their production methods are shifting from conventional chemicals to fermentation, driven by green process strategies, environmental regulations, cost feasibility, etc. Separating formed acid from the fermentation broth is a primary technological barrier. Conventional methods are complex and impose environmental issues. A promising approach, `Chemodialysis,' capable of transforming the techno-economical feasibility of acid recovery scenario by reducing the number of steps, needs further investigation. This work evaluates scalable hollow fiber membranes based on poly(2,5-benzimidazole) (ABPBI) for chemically assisted dialysis, viz., Chemodialysis. Sorption analyses of commercially significant organic acids (acetic, lactic, and glycolic acid) and nonacidic solutes (NaCl and glucose) were performed using conventional flat sheet samples to assess their role in governing permeation characteristics. The transport properties of acids in the presence of NaCl and glucose as co-solutes were analyzed using hollow fiber membranes. The high selectivity of acid over nonacidic solutes ranges from 400-22,400, coupled with high acid permeability, enhances the applicability of Chemodialysis for the separation of acids using hollow fiber membranes. The fluxes of acids (acetic, glycolic, and lactic) through dense, similar to 100 mu m thick, scalable hollow fiber membranes ranging from 10.9 to 13.12 g/m(2)h are highly appreciable.
Keywords: 5-benzimidazole); Acid separation; Chemodialysis; Hollow fiber membranes; Organic acids; Poly(2